Health and social care use, costs, and satisfaction among key workers accessing Resilience Hub support during the COVID-19 pandemic - Aleix Rowlandson; Filippo Varese; Linda M. Davies; Paul French; Kate Allsopp; Lesley-Anne Carter; Daniel Hind; Katherine McGuirk; Alan Barrett; Gita Bhutani; Fay Huntley; Joanne Jordan; et al. (BMC Health Services Research)
Abstract Key workers are vulnerable to adverse mental health. To ensure service sustainability during COVID-19, Resilience Hubs were established across England offering outreach, screening, and mental health support. This evaluation aimed to describe wider service use, associated costs, and satisfaction among Hub clients (key workers) accessing Hub support. Clients accessing support across four Hubs were invited to complete a service use questionnaire, between 5 and 8 months post referral, collecting satisfaction, wider service use and cost data. Exploratory linear regression assessed the relationship between demographic variables and service use. Most Hub clients reported Hub contact post referral (219/299, 73.2%), with many accessing mental health support (171/299, 57.2%) or on waitlists (34/299, 11.4%). Satisfaction was high, with median helpfulness rated 92 (out of 100), and many stating that Hubs either fully (148/299, 49.5%) or partially (54/299, 18.1%) met their needs. Mental health support accounted for most service use, with higher total service use and costs when including Hub services (£514 versus £213). Key workers have complex needs. Hub services helped clients to access support, with high reported satisfaction indicating that Hubs met clients needs. Further research is required to assess how service use varies according to occupation or demographic characteristics, and whether Hubs are clinically and cost-effective.